2020
DOI: 10.5761/atcs.oa.19-00162
|View full text |Cite
|
Sign up to set email alerts
|

Changeover Trial of Febuxostat and Topiroxostat for Hyperuricemia with Cardiovascular Disease: Sub-Analysis for Chronic Kidney Disease (TROFEO CKD Trial)

Abstract: Background: The TROFEO trial demonstrated that febuxostat causes greater and more rapid reduction of serum uric acid (s-UA) than topiroxostat. We compared these drugs in patients with chronic kidney disease (CKD) by sub-analysis of the TROFEO trial. Methods: This sub-analysis targeted patients with an estimated glomerular filtration rate (eGFR) ≤60 mL/min/1.73 m 2 . The primary endpoint was the s-UA level. Secondary endpoints included creatinine, eGFR, urinary albumin, cystatin-C, oxidized low-density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This suggests that while both medications effectively lowered SUA levels in hyperuricemia patients, they did so to a comparable extent, without a discernible difference between the two treatment groups. Similarly, according to the TROFEO study [5] there was no significant difference in serum uric acid levels between the Topiroxostat and febuxostat groups either before or after treatment, but they also concluded reduction of serum uric acid was more rapid with febuxostat than topiroxostat which was not present in our study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This suggests that while both medications effectively lowered SUA levels in hyperuricemia patients, they did so to a comparable extent, without a discernible difference between the two treatment groups. Similarly, according to the TROFEO study [5] there was no significant difference in serum uric acid levels between the Topiroxostat and febuxostat groups either before or after treatment, but they also concluded reduction of serum uric acid was more rapid with febuxostat than topiroxostat which was not present in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, Kario K et al in 2021 found that while urinary albumin-creatinine ratio (UACR) significantly decreased from baseline to 24 weeks with topiroxostat (-20.8%; p = 0.021), it did not significantly change with febuxostat (-8.8%; p = 0.362) [14] . However, findings from the TROFEO CKD trial study suggested that febuxostat demonstrated more potent renal protective effects than topiroxostat [15] . The eGFR analysis from Table 4 indicates a statistically significant improvement in eGFR values within the Topiroxostat group over the 12-week period, with a mean improvement of 0.6375 mL/min/1.73 m 2 and a p-value of 0.00034.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, related results have shown that topiroxostat ameliorates kidney injury in puromycin aminonucleoside nephrosis rats by reducing oxidative stress and the UA concentration [ 135 , 136 ]. However, febuxostat had stronger renoprotective and antioxidant effects than topiroxostat in patients with hyperuricemia and chronic kidney disease (CKD) [ 137 ].…”
Section: Xanthine Oxidase Inhibition Studiesmentioning
confidence: 99%
“…Moreover, febuxostat was more effective and faster than allopurinol in achieving the serum uric acid target in patients with gout [36]. Similarly, febuxostat has an advantage over topiroxostat in cardiorenal protection in hyperuricemic patients with cardiovascular disease [37,38]. Recently, there have been only two reports on the treatment of SI-AKI with febuxostat showing that febuxostat improves the prognosis of SI-AKI animals through antioxidant stress and anti-inflammation [20,21].…”
Section: Discussionmentioning
confidence: 99%